PENGEMBANGAN INSTRUMEN SOAL BERBASIS GOOGLE FORM PADA MATERI SISTEM PERNAPASAN PADA MANUSIA KELAS VIII MTS - Wahdatul Wahidah; Lina Arifah fitriyah; Nur Kuswanti (FKIP, Universitas Billfath Lamongan, 2022)
The question instrument is one of the evaluation tools. This study uses the ADDIE analysis development model. The data collection instrument used is a cognitive test of 20 questions and a questionnaire validation sheet. The purpose of this study was to determine the results of the development after the process of theoretical and empirical validity. The results of the research show that the test instrument for testing the validity, reliability, discriminating power, level of difficulty and distractors obtained a valid instrument as many as 10 items from 20 questions, reliability (r11) obtained is 0.856 with a high level of reliability, for power the difference is that 20 items are categorized as